1988
DOI: 10.1002/hrm.3930270102
|View full text |Cite
|
Sign up to set email alerts
|

New challenges for Japanese multinationals: Is organization adaptation their achilles heel?

Abstract: As the number, size, and complexity of Japanese multinational companies' (MNCs) overseas operations increase, many of them have begun to realize that they face some fundamental and difficult organizational challenges. Drawing on research undertaken with several large and successful Japanese MNCs, the authors define the nature and source of some of these organizational challenges, and describe some approaches that can be taken to resolving them. The article starts with a brief assessment of the traditional orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…Bartlett and Ghoshal (1989) and Bartlett and Yoshihara (1988) perceive this characteristic of Japanese companies as the evil of Japanese companies in concentrating resources and power in the home headquarters and not focusing on the subsidiary. More research is needed to answer whether this is actually a unique phenomenon of Japanese companies, or a phenomenon perceived during the transition of the overseas subsidiary's enhancement of functions.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Bartlett and Ghoshal (1989) and Bartlett and Yoshihara (1988) perceive this characteristic of Japanese companies as the evil of Japanese companies in concentrating resources and power in the home headquarters and not focusing on the subsidiary. More research is needed to answer whether this is actually a unique phenomenon of Japanese companies, or a phenomenon perceived during the transition of the overseas subsidiary's enhancement of functions.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Japanese companies tend to send more expatriates abroad from the home headquarters in comparison to the multinational corporations of Europe and the USA (Bartlett & Yoshihara, 1988;Kopp, 1994aKopp, , 1994b. 1 However, it has been shown that the numbers of expatriates in overseas subsidiaries of Japanese companies decreased in the first half of the 1990s (Beamish & Inkpen, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations